2003
DOI: 10.1142/s021812740300834x
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Bifurcations: A Novel Mechanism for the Sudden Onset of Chaos in Dry Friction Oscillators

Abstract: Recent investigations of nonsmooth dynamical systems have resulted in the study of a class of novel bifurcations termed as sliding bifurcations. These bifurcations are a characteristic feature of so-called Filippov systems, that is, systems of ordinary differential equations (ODEs) with discontinuous right-hand sides. In this paper we show that sliding bifurcations also play an important role in organizing the dynamics of dry friction oscillators, which are a subclass of nonsmooth systems. After introducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
88
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 31 publications
2
88
0
2
Order By: Relevance
“…It was shown that the so-called corner-collision, sliding and grazing bifurcations all belong to this class. 9,[26][27][28][29][30][31][32] To investigate the various types of bifurcation, a normal form map may be constructed ͑see, e.g., Refs. 26-29͒.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the so-called corner-collision, sliding and grazing bifurcations all belong to this class. 9,[26][27][28][29][30][31][32] To investigate the various types of bifurcation, a normal form map may be constructed ͑see, e.g., Refs. 26-29͒.…”
Section: Introductionmentioning
confidence: 99%
“…One of the intriguing features of hybrid systems is the possibility of a sudden onset of chaotic dynamics. Such scenarios have been observed, for instance, in the context of modelling DC/DC power converters Banerjee et al (1998); Banerjee and Verghese (2001), and dry-friction oscillators di Bernardo et al (2003). The onset of chaotic dynamics in these systems was shown to have been triggered by a nontrivial interaction between a system Ω−limit set and the so-called switching surface.…”
Section: Introductionmentioning
confidence: 91%
“…Early interest in discontinuity-induced bifurcations in such systems has naturally focused on regions of a switching manifold that are attractive, and where sliding occurs. The result is that periodic orbits can acquire segments of sliding by so-called sliding bifurcations (di Bernardo et al, 2003(di Bernardo et al, , 2008). The scenario of sliding in a region where solutions are repelled from the switching manifold (sometimes called escaping), appears at first to be of less interest dynamically, because one expects solutions to evolve away from the discontinuity.…”
Section: Introductionmentioning
confidence: 99%